The Effect of Ocimum basilicum L. and Its Main Ingredients on Respiratory Disorders: An Experimental, Preclinical, and Clinical Review - Aminian, Ahmad Reza; Mohebbati, Reza; Boskabady, Mohammad Hossein (Frontiers in Pharmacology, 2022)
Ocimum basilicum L. (O. basilicum) and its constituents show anti-inflammatory, immunomodulatory, and antioxidant effects. The plant has been mainly utilized in traditional medicine for treatment of respiratory disorders. In the present article, effects of O. basilicum and its main constituents on respiratory disorders assessed by experimental and clinical studies, were reviewed. Relevant studies were searched in PubMed, Science Direct, Medline, and Embase databases using relevant keywords including “Ocimum basilicum”, “basilicums”, “linalool” “respiratory disease”, “asthma”, “obstructive pulmonary disease”, “bronchodilatory”, “bronchitis”, “lung cancer”, “pulmonary fibrosis” and other related keywords. The reviewed articles showed both relieving and preventing effects of the plant and its ingredients on obstructive pulmonary diseases such as chronic obstructive pulmonary diseases (COPD) and asthma and other respiratory disorders such as bronchitis, aspergillosis tuberculosis, and lung cancer. The results of the reviewed articles suggest the therapeutic potential of O. basilicum and its constituent, linalool, on respiratory disorders.